Long-term control of Coxiellosis in sheep by annual primary vaccination of gimmers. Issue 35 (19th August 2022) - Böttcher, Jens; Bauer, Benjamin U.; Ambros, Christina; Alex, Michaela; Domes, Ursula; Roth, Sabine; Boll, Kerstin; Korneli, Martin; Bogner, Karl-Heinz; Randt, Andreas; Janowetz, Britta
Abstract: Coxiella (C.) burnetii, a Gram-negative intracellular bacterium, causes Q fever in humans and Coxiellosis in animals. Ruminants are a primary source of human infection with C. burnetii . In 2013, vaccination was implemented in a sheep flock with 650 ewes associated with two outbreaks of Q fever in humans in 2008 and 2012. Only gimmers (yearlings) received two doses of a commercial C. burnetii phase I whole cell vaccine three weeks apart (primary vaccination) without any revaccination. Vaginal and nasal swabs collected shortly after lambing were tested by qPCR. Additionally, a group of non-vaccinated sentinels was serologically monitored for phase I (PhI), II (PhII) antibodies and for Interferon γ (IFN-γ) after stimulation of whole blood cells with PhII-antigen with and without an IL-10-neutralizing monoclonal antibody. In 2021, 679 sera collected in 2014–2021 were retested retrospectively with three commercial ELISA kits and one batch of an in-house PhI/PhII-ELISA. A low-level shedding of C. burnetii (<10 3 mean C. burnetii /swab) was observed until 2014. In 2021 C. burnetii was detected in two animals (<10 3.1 C. burnetii /swab), but vaginal swabs collected at two subsequent lambing seasons remained negative. Seroconversion of sentinels was detected until 2017. However, the retrospective analysis of sentinels in 2021 revealed additional single seropositive animals from 2018 to 2021. IFN-γ reactivity was observed during the whole study period; it peaked in 2014 and in 2018 and decreased thereafter. The sporadic detection of C. burnetii and the immune responses of sentinels suggested that a subliminal infection persisted despite vaccination. Nevertheless, vaccination of gimmers prevented the development of a major outbreak, it controlled the infection and reduced the risk of human infection.